The Program - Young, Suzanne (New York : Simon Pulse, 2016)
"After discovering that everything she's ever known including her own identity has been a lie, Quinlan McKee is determined to find out the truth about her past. But in her search for answers, she discovers a cover-up more chilling than she can imagine. An epidemic is coming, and there's no way to stop it"--
Sequel to: The Remedy.
Companion book to: The Program and The Treatment.
HL 690
Keywords: Death -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Memory -- Juvenile fiction; Epidemics -- Juvenile fiction; Identity -- Fiction; Death -- Fiction; Suicide -- Fiction; Grief -- Fiction; Epidemics -- Fiction; Science fiction